Mendeteksi Indikasi Kecurangan Laporan Keuangan dengan Metode F-Score Menggunakan Model Fraud Pentagon - Maherliana, Ika; Ariyanto, Dodik (E-Jurnal Akuntansi, 2023)
Fraud in financial reports can occur because there is pressure on agents, thereby encouraging them to commit fraudulent acts whose aim is to show that the company is performing well. This research aims to test the fraud pentagon theory in detecting indications of fraudulent financial statements. Testing was carried out on mining companies registered on the IDX during the 2016 - 2020 period. Sample selection was carried out using a purposive sampling technique with a final sample of 21 mining companies. Data analysis in this study used multiple linear regression analysis. The research results show that external pressure has a negative effect on detecting indications of financial report fraud and ineffective monitoring has a positive effect on detecting indications of financial report fraud. This research provides implications for all parties who need information to provide an assessment of the opportunities for indications of financial statement fraud in mining companies by considering the factors that influence it. Keywords: Fraud Pentagon Theory; Fraudulent Financial Reporting;  Mining Compines